2018
DOI: 10.21470/1678-9741-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Patent Foramen Ovale versus Medical Therapy after Cryptogenic Stroke: Meta-Analysis of Five Randomized Controlled Trials with 3440 Patients

Abstract: ObjectiveWe aimed to determine whether patent foramen ovale closure reduces the risk of stroke, also assessing some safety outcomes.IntroductionThe clinical benefit of closing a patent foramen ovale after a cryptogenic stroke has been an open question for several decades, so that it is necessary to review the current state of published medical data in this regard.MethodsMEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LI-LACS, Google Scholar and reference lists of relevant articles were searched for randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(37 reference statements)
2
4
0
Order By: Relevance
“…In a recent meta-analysis, meta-regression analyses showed that the older patients or proportion of participants with hypertension or atrial septal aneurysm presented higher risks of stroke. 31 These results are in line with our findings concerning the age. Similarly, the presence of atrial septal aneurysm had no impact on the primary outcome in both the meta-analyses.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent meta-analysis, meta-regression analyses showed that the older patients or proportion of participants with hypertension or atrial septal aneurysm presented higher risks of stroke. 31 These results are in line with our findings concerning the age. Similarly, the presence of atrial septal aneurysm had no impact on the primary outcome in both the meta-analyses.…”
Section: Discussionsupporting
confidence: 92%
“…Paradoxical embolism from the right to the left side of the heart can occur through a PFO, causing a cryptogenic stroke or embolic stroke of an undetermined source in an otherwise healthy adult. There was a debate on the long-term benefits of closure; however, data from the randomized evaluation of the recurrent stroke comparing PFO closure to established current standard of care treatment (RESPECT) trial and two randomized trials (patent foramen ovale closure or anticoagulants versus antiplatelet therapy to prevent stroke recurrence (CLOSE) and reduction by dutasteride of prostate cancer events (REDUCE)) and several meta-analyses of these studies have clarified that there is a benefit to the closure of PFO [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…A number of randomized trials have demonstrated that PFO closure is superior to medical therapy with antiplatelet therapy alone [9][10][11]. Multiple studies, including a meta-analysis of multiple trials (CLOSE 2017, CLOSURE 2013, RESPECT 2013, and PC 2013), showed that, in patients who had a cryptogenic stroke, thought to be due to a PFO, those assigned to device closure and antiplatelet therapy had reduced incidence of recurrent strokes and brain infarctions compared to those assigned to antiplatelet therapy alone [9][10][11]. In one study by Sondergaard et al, device-related complications occurred in 1.6% of the PFO closure group and 6.6% developed atrial fibrillation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After peeling, they like to use their small hands to tear it. Causes serious bacterial infections [6][7].…”
Section: ) Coccidia Angular Cheilitismentioning
confidence: 99%